The gut microbiota modulates responses to anti–PD-1 and chemotherapy combination therapy and related adverse events in patients with advanced solid tumors - Wu, Zhaozhen; Zhang, Sujie; Li, Lingling; Huang, Ziwei; Huang, Di; Hu, Yi (Frontiers in Oncology, 2022)
Background: Immune checkpoint inhibitors（ICIs）targeting programmed cell death protein 1 (PD-1) have shown promising prospect in treating different malignancies, and several studies reported gut microbiota modulated the response to ICIs in melanoma, non-small cell lung cancer(NSCLC), renal cell cancer（RCC）and hepatocellular carcinoma (HCC) , but data in other cancer types and ICIs-combined therapy are limited. Method: Stool samples were collected from cancer patients who received anti-PD-1 and chemotherapy combination treatment and were analysed by faecal metagenomic sequencing. The microbiota diversity and composition were compared between the responder (R) and non-responder (NR) groups and the adverse event (AE) vs. the non-AE (NAE) groups. Additionally, associated functional genes and metabolic pathways were identified. Results: At baseline, the microbiota diversity of the groups was similar, but the genera Parabacteroides, Clostridia bacterium UC5.1_2F7 and Bifidobacterium dentium were enriched in the R group, while Bacteroides dorei and 11 species of Nocardia were enriched in the NR group. At 6 weeks, the beta diversity was significantly different between the R and NR groups. Further analysis found that 35 genera, such as Alipes, Parabacteroides, Phascolarctobacterium, Collinsella, Ruminiclostridium, Porphyromonas, Butyricimonas and several genera of the Fibrobacteraceae family, were frequently distributed in the R group, while 17 genera, including Enterococcus, Lachnoclostridium, Hungatella, Bilophila, and several genera of the Pseudonocardiaceae and Beijerinckiaceae families, were more abundant in the NR group. Additionally, pathway analysis revealed functional differences in the gut microbacteria in the R group, including the enrichment of anabolic pathways and DNA damage repair (DDR) pathways. Dynamic comparisons of the bacterial composition showed that the abundance of Weissella significantly increased in the R group at 6 weeks and the abundance of Fusobacterium and Anaerotruncus significantly increased in the NR group at 12 weeks. LEfse analysis indicated that bacteria of the phylum Bacteroidetes, especially Bacteroides, were enriched in the NAE group, while flora of the phylum Firmcutes, such as Faecalibacterium prausnitzii, Bacteroides fragilis and Ruminococcus lactaris, were enriched in the AE group. Conclusion: Beta diversity and differences in the gut microbiota modulated AEs and the response to anti-PD-1 blockade combined with chemotherapy, by regulating related anabolic and DDR pathways.